STUDI TENTANG KOMPETENSI WIRAUSAHA, KEMAMPUAN MENGINDERA PASAR DAN KEUNGGULAN BERSAING UNTUK MENINGKATKAN KINERJA PEMASARAN PADA USAHA MIKRO, KECIL DAN MENENGAH DI SEMARANG - Pratomo, Mohammad Rizky Teguh; Widiyanto, Ibnu (Faculty of Economics and Business Diponegoro University, 2015)
The background of this study is the sales decline of Micro and Small Business Enterprise (MSBE) in Semarang, and the controversy of the research findings about the influences of Entrepreneurial Competence, Market Sensing Capability and Competitive Advantage towards Marketing Performance. The number of sample in this study was 385 Micro and Small Business Enterprise (MSBE) in Semarang, with purposive sampling technique. The questionaires was distributed on March 2015. The data collected from the questionnaires was then processed using multiple regression method.The results of this study show that the two of the independent variables have positive influences to the competitive advantage and market performance. Entrepreneurial competence has the biggest influence to competitive advantage and competitive advantage has the biggest influence to market performance. This results support the previous research that entrepreneurial competence and market-sensing capability has a significant positive influence to competitive advantage and competitive advantage has proven to be an intervening variable to market performance. The conclusion of this study shows that entrepreneurial competence and market-sensing capability has positive and significant influences to competitive advantage and an indirect influence to market performance.